4D-tracking in the 10-ps range: A technological perspective - Lai, Adriano (Frontiers in Physics, 2022)
The present paper focuses on recent and ready-to-come advancements concerning high resolution 4D-tracking with a perspective approach. 4D-tracking techniques (particle tracking with timing information for each detection point) have revealed necessary for the next and next-to-next generations of high-energy physics experiments to cope with the increasing luminosity and consequent event pile-up in the beam collision region. Such decisive challenge concerns both detection and processing technologies at an unprecedented level of difficulty. Besides the high performance required in space-time measurement precision (some 10 ps resolution in timing and about 10 µm resolution in space), an extremely high radiation hardness is demanded for such technologies (expected particle Fluences of about 1017 1-MeV neutron equivalent per cm2). Emerging experimental solutions for sensors and electronics against such challenge are here presented.